Indonesian Learners' Requests in English: A Speech-Act Based Study - F.X. Nadar (Humaniora, 1998)
This paper investigates requests by Indonesian learners based on speech act theories. It attempts to find the charaderistics of the requests, and discuss the findings from the view points of forms and politeness strategy. This essay consists of five main parts. They are the introduction, brief theoretical aspects of making requests, methodology, result and discussion and conclusion. Language is a means of communication, and people use language for various reasons, Finegan, et al.(1992:3) state that language has been viewed as a vehicle of thought, a system of expression that mediates the transfer of thought from one person to another. They also claim (p.305) that "language is principally a tool for doing things" and describe that through language people do things such as: propose marriage, impose a life sentence, swear to tell the truth, fire an employee and so on. Learning how language is used is commonly associated with the study of speech acts. Speech acts are "actions that are carried out through language- (Finegan, et 81.,1992:307). Various tasks are accomplished by means of language, and linguists have different ways of explaining about speech acts.